2013
DOI: 10.3109/09638288.2012.738760
|View full text |Cite
|
Sign up to set email alerts
|

Gait characteristics of multiple sclerosis patients in the absence of clinical disability

Abstract: MS patients with no clinical disability have discrete changes in gait that can be evidenced by perceived impact on walking and kinematic evaluation, mainly of ankle movement. Moreover, there is a decrease in perceived balance confidence and an increase in perceived fatigue, which are correlated despite having different origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Briefly, in cases of motor fatigue, although some authors found an association between self-reported fatigue scores and gait parameters [21,137,138,189,193] or power generation [87]; others failed to detect such a relationship [41,46,136,148,236]. In a similar manner, cognitive measures were the subject of some studies.…”
Section: Objective Measuresmentioning
confidence: 96%
“…Briefly, in cases of motor fatigue, although some authors found an association between self-reported fatigue scores and gait parameters [21,137,138,189,193] or power generation [87]; others failed to detect such a relationship [41,46,136,148,236]. In a similar manner, cognitive measures were the subject of some studies.…”
Section: Objective Measuresmentioning
confidence: 96%
“…Increased hip flexion [2], knee flexion [2,5], and ankle plantarflexion [2,3] at initial foot contact and early stance, and decreased hip extension [2,5], knee extension [2] and ankle plantarflexion [2,11] around late stance are commonly reported features, with the decreased hip extension around late stance and decreased knee extension (i.e. increased flexion) around late swing and foot contact likely contributing to decreases in step length and walking speed.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies examining the association between gait performance and perceived fatigue have presented mixed and limited results. Huisinga et al [ 18 ] found a correlation between fatigue measured by the Fatigue Severity Scale and deficits in ankle power generation at late stance, in mild disability MS participants (average EDSS = 2.6).In contrast, Noguiera et al did not observe any interaction between the fatigue and ankle motion in 12 PwMS [ 19 ]. Sacco et al [ 20 ] found a correlation between temporal-spatial parameters of gait (speed, cadence and stride length) collected by the GAITRite mat and fatigue (measured by the Wurzburg Fatigue Inventory for MS), revealing a significant negative correlation between velocity (r = -0.54), cadence (r = -0.44) and stride length (r = -0.5).…”
Section: Introductionmentioning
confidence: 99%